2020
DOI: 10.3390/nu12040925
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Moderate-Intensity Continuous or High-Intensity Interval Training on Adipogenesis and Browning of Subcutaneous Adipose Tissue in Obese Male Rats

Abstract: This study compares the effect of two types of exercise training, i.e., moderate-intensity continuous training (MICT) or high-intensity interval training (HIIT) on the browning of subcutaneous white adipose tissue (scWAT) in obese male rats. Effects on fat composition, metabolites, and molecular markers of differentiation and energy expenditure were examined. Forty male Wistar rats were assigned to lean (n = 8) or obese (n = 32) groups and fed either a standard chow or high-fat obesogenic diet for 10 weeks. Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 73 publications
(89 reference statements)
4
39
1
3
Order By: Relevance
“…Zhang et al [ 35 ] revealed that IR improvements were related to the increased activity of PPAR α , CPT1, and CD36 protein. The research on obese mice has proved similar outcomes as well [ 36 ]. All these outcomes from others indirectly confirmed that oral administration metabolitin contributed to biological regulation.…”
Section: Discussionmentioning
confidence: 77%
“…Zhang et al [ 35 ] revealed that IR improvements were related to the increased activity of PPAR α , CPT1, and CD36 protein. The research on obese mice has proved similar outcomes as well [ 36 ]. All these outcomes from others indirectly confirmed that oral administration metabolitin contributed to biological regulation.…”
Section: Discussionmentioning
confidence: 77%
“…After a 10-week HIIT program (5 × (2 min at 80–90%VO 2 max/1 min 30–35%VO 2 max)), Shanaki et al [ 39 ] observed lower fasting glycemia, fasting insulinemia and HOMA-IR in Wistar rats with HFD-induced obesity and diabetes. Conversely, Khalafi et al [ 52 ] did not detect any change in fasting insulinemia. Here, we did not observe any effect of HIIT alone on fasting glucose and insulin concentration and insulin responses during OGTT, but the HIIT + T63 combination significantly improved the glycemic responses during OGTT.…”
Section: Discussionmentioning
confidence: 92%
“…Seven of the studies in animals identified in the systematic review that used a normal diet [11][12][13][14][15]40,41] provided data for a meta-analysis showing no effect of chronic exercise on UCP1 mRNA (p > 0.05). An additional meta-analysis using data from four studies [11,[42][43][44] for UCP1 protein expression showed a significant impact of chronic exercise in normal diet animals (Std = 0.41, CI = −0.01-0.83, p = 0.05, Figure 5). With respect to acute exercise (i.e.…”
Section: Resultsmentioning
confidence: 99%